(3GdSQjGdjI aj eUQ(B/ s ((3eQcR GdTGQbI ddEHOGY GdacQj, hRGQI GdKbGaI h GdEYdGe; s)
Study of the surrealism art movement in Egypt. Ramses Younan, George Henein, Kamel AlTalmisani, Ratib Siddique, Angelo de Riz, Fouad Kamel, Aida Shhatah, Sadiq Muhammad, Hajadya, Sa'ad AlKhadim, Ali Zahdi Hastiri, Jalal AlSyed, Izzaldin Najib, Alaa' AlDeeb, Mukhtar AlAttar, Abdul Aal AlHamamasi, Salah Faiq.
Arabic
Keywords: N5300-7418 Visual Arts- History; Surrealism; Egypt